TEACHING SPEAKING BY USING 'ELSA AI' TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 42 PALEMBANG - Salsabilla, Dinda; Tahrun; Rosmiyati, Evi (Universitas PGRI Palembang, 2024)
This study investigates the effectiveness of the ELSA Speak application in enhancing English speaking skills among eighth-grade students at SMP Negeri 42 Palembang. Employing a quantitative method with a quasi-experimental design (one-group pre-test and post-test design), the research involved 34 students. The instruments used included a pre-test, treatment, and post-test. The results indicate that using ELSA Speak effectively improves English pronunciation skills compared to traditional learning methods. The average pre-test score of the students was 64.9118, which increased to 85.5882 in the post-test, showing an improvement of 31.82%. Hypothesis testing revealed a significance value of 0.000, indicating a significant effect of using ELSA Speak on students' performance improvement. The Cohen's Kappa value of 0.809 demonstrates excellent inter-rater reliability, which positively supports the validity of the obtained results. Future research should examine the long-term effects of ELSA Speak on fluency and confidence, compare it with other language learning tools, and involve larger, more diverse samples for broader insights.